THE EFFECTIVENESS OF LMS ASSISTED STAD LEARNING MODEL ON SOCIAL STUDIES LEARNING OUTCOMES FOR ELEMENTARY SCHOOL: LITERATURE REVIEW - Nurul Ragil Ananda (Universitas Pendidikan Indonesia, 2022)
This research aims to examine the effectiveness of the implementation of cooperative learning model type Student Teams Achievement Division (STAD) on the social studies learning outcomes of students grade V elementary school. The type of research conducted is a literature review. This literature review research analyzes in depth in order to obtain objective research results on student teams achievement division (STAD) learning model to improve the social studies learning outcomes for students in grade V elementary school. The data used in this research was obtained from leading journal sites, such as Sinta, Scopus, Google Scholar, and DOAJ. In this research, researcher obtained 2600 articles with related titles, then the results of the articles were reduced according to the criteria set out in the selection of data articles, so that 35 articles were selected that were relevant to the purpose of the research. Based on the results of the analysis of the article, it can be concluded that the application of cooperative learning model type Student Teams Achievement Division effectively used in social studies learning in grade V elementary school to improve student learning outcomes, both in terms of cognitive, affective, and skills.